Xerxes and Demaratus in Herodotus’ Histories: intersecting identities between Greek and barbarian (Circe de clásicos y modernos, 2018)
The paper offers a discursive analysis of the dialogue between Xerxes and Demaratus, prior to the Persian attack on the Greeks, as dramatized in Herodotus 7. 101-104. The interaction between the interlocutors is closely explored in order to: a) outline the discursive roles and argumentative strategies deployed by either participant, b) address the social identities constructed throughout the interaction and the prospective, albeit hazy, delineation of a Greek and barbarian éthos, c) speculate on the significance of the episode in the context of the Histories and the ideological implications of the alleged relationship between the Persian autocracy and Spartan kingship.
Keywords: Herodotus; Xerxes; Demaratus; discourse analysis